Multicultural Education and Its Relevance to the Goals of Islamic Education - Madhar Amin (STIT Attaqwa, 2024)
Islamic education prioritizes how to develop cognitive, affective, and also human emotions while still based on Islamic teachings. It is all for no other purpose than to explore Islam in individual and group life. The connection between Islamic and multicultural education will be a solution to the reality of various cultures as a form of potential development process that respects plurality and heterogeneity as a consequence of cultural, ethnic, tribal, and religious diversity. The existence of cultural plurality in Indonesia makes multicultural education very urgent. The focus of this research is on how the nature of multicultural education and its relevance to the goals of Islamic education. This is based on research that has been done before on Multicultural Education and the Nature of Islamic Education Goals, the author took the initiative to conduct research by analyzing the two studies to find common ground between multicultural education and Islamic education goals so that it can be known how the relevance between the two. The results of this study show that multicultural education is relevant to the goals of Islamic education, which essentially both have the aim of forming a peaceful and harmonious life in the midst of a society where there are differences in religion, ethnicity, tribe, language, and culture.